Atlanta and Environs : A Chronicle of Its People and Events, 1880s-1930s - Garrett, Franklin M. (Franklin Miller), 1906- (Book collections on Project MUSE., 1969)
Atlanta and Environs is, in every way, an exhaustive history of the Atlanta Area from the time of its settlement in the 1820s through the 1970s. Volumes I and II, together more than two thousand pages in length, represent a quarter century of research by their author, Franklin M. Garrett a man called "a walking encyclopedia on Atlanta history" by the Atlanta Journal-Constitution. With the publication of Volume III, by Harold H. Martin, this chronicle of the South's most vibrant city incorporates the spectacular growth and enterprise that have characterized Atlanta in recent decades. The work is arranged chronologically, with a section devoted to each decade, a chapter to each year. Volume I covers the history of Atlanta and its people up to 1880 ranging from the city's founding as "Terminus" through its Civil War destruction and subsequent phoenixlike rebirth. Volume II details Atlanta's development from 1880 through the 1930s including occurrences of such diversity as the development of the Coca-Cola Company and the Atlanta premiere of Gone with the Wind. Taking up the city's fortunes in the 1940s, Volume III spans the years of Atlanta's greatest growth. Tracing the rise of new building on the downtown skyline and the construction of Hartsfield International Airport on the city's perimeter, covering the politics at City Hall and the box scores of Atlanta's new baseball team, recounting the changing terms of race relations and the city's growing support of the arts, the last volume of Atlanta and Environs documents the maturation of the South's preeminent city.